Co-occurring pathogenic variants in 6q27 associated with dementia spectrum disorders in a Peruvian family - Alvarez, Karla Lucia F.; Aguilar-Pineda, Jorge Alberto; Ortiz-Manrique, Michelle M.; Paredes-Calderon, Marluve F.; Cardenas-Quispe, Bryan C.; Vera-Lopez, Karin Jannet; Goyzueta-Mamani, Luis D.; Chavez-Fumagalli, Miguel Angel; Davila-Del-Carpio, Gonzalo; Peralta-Mestas, Antero; Musolino, Patricia L.; Lino Cardenas, Christian Lacks (Frontiers in Molecular Neuroscience, 2023)
Evidence suggests that there may be racial differences in risk factors associated with the development of Alzheimer’s disease and related dementias (ADRD). We used whole genome sequencing analysis and identified a novel combination of three pathogenic variants in the heterozygous state (UNC93A: rs7739897 and WDR27: rs61740334; rs3800544) in a Peruvian family with a strong clinical history of ADRD. Notably, the combination of these variants was present in two generations of affected individuals but absent in healthy members within the family. In silico and in vitro studies have provided insights into the pathogenicity of these variants. These studies predict the loss of function of the mutant UNC93A and WDR27 proteins which induced dramatic changes in the global transcriptomic signature of brain cells, including neurons, astrocytes, and especially pericytes and vascular smooth muscle cells, and thus indicating that the combination of these three variants may affect the neurovascular unit. In addition, key known molecular pathways associated with dementia spectrum disorders were enriched in brain cells with low levels of UNC93A and WDR27. Our findings have thus identified a genetic risk factor for familial dementia in a Peruvian family with an Amerindian ancestral background.